Multilayered Si Nanoparticle/Reduced Graphene Oxide Hybrid as a High‐Performance Lithium‐Ion Battery Anode. (24th September 2013) - Chang, Jingbo; Huang, Xingkang; Zhou, Guihua; Cui, Shumao; Hallac, Peter B.; Jiang, Junwei; Hurley, Patrick T.; Chen, Junhong
<x xml:space="preserve">Abstract</x> Multilayered Si/RGO anode nanostructures, featuring alternating Si nanoparticle (NP) and RGO layers, good mechanical stability, and high electrical conductivity, allow Si NPs to easily expand between RGO layers, thereby leading to high reversible capacity up to 2300 mAh g−1 at 0.05 C (120 mA g−1) and 87% capacity retention (up to 630 mAh g−1) at 10 C after 152 cycles. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>